Resequencing the Yaroslavl cattle genomes reveals signatures of selection and a rare haplotype on BTA28 likely to be related to breed phenotypes. (16th June 2022) - Ruvinskiy, Daniil; Igoshin, Alexander; Yurchenko, Andrey; Ilina, Anna V.; Larkin, Denis M.
Abstract: The genomes of local livestock could shed light on their genetic history, mechanisms of adaptations to environments and unique genetics. Herein we look into the genetics and adaptations of the Russian native dairy Yaroslavl cattle breed using 22 resequenced individuals and comparing them with two related breeds (Russian Kholmogory and Holstein), and to the taurine set of the 1000 Bull Genomes Project (Run 9). HapFLK analysis with Kholmogory and Holstein breeds (using Yakut cattle as outgroup) resulted in 22 regions under selection ( q ‐value < 0.01) on 11 chromosomes assigned to Yaroslavl cattle, including a strong signature of selection in the region of the KIT gene on BTA6. The F ST (fixation index) with the 1000 Bull Genomes Dataset showed 48 non‐overlapping top (0.1%) F ST regions of which three overlapped HapFLK regions. We identified 1982 highly differentiated ( F ST > 0.40) missense mutations in the Yaroslavl genomes. These genes were enriched in the epidermal growth factor and calcium‐binding functional categories. The top F ST intervals contained eight genes with allele frequencies quite different between the Yaroslavl and Kholmogory breeds and the rest of the 1000 Bull Genomes Dataset, including KAT6B, which had a nearly Yaroslavl breed‐specific deleterious missense mutation with the highest F ST in our dataset (0.99). This gene is a part of a long haplotype containing other genes from F ST and hapFLK analyses and with a negative association with weight and carcass traits according to the genotyping of 30 phenotyped Yaroslavl cattle individuals. Our work provides the industry with candidate genetic variants to be focused on in breed improvement efforts.